(untitled) (International Journal of Physiology, 2019)
Background Patient suffering from hypertension are at increased incidence of suffering from increase in size of left ventricular mass (hypertrophy) due to associated risk factor like male sex, advanced age, males including addiction to smoking and alcohol. Measurement of left ventricular mass index helps in detecting the increase in size of left ventricular mass (hypertrophy). Objectives To evaluate increase in size of left ventricular mass (hypertrophy) in relation to ventricular mass index of left ventricle in hypertensive patients. Method A total 100 patients were grouped into 2 groups and named as Group I who served as Normal-Left ventricular mass index-N-LVMI) and Group II who served as Increased Left ventricular mass index-I-LVMI (More than 118g/m2 in males and 109 g/m2 in females. All patients were evaluated for past history and related cardiovascular parameters. About 67 patients among 100 had normal LVMI and 33 patients as per Penn’s convention formula had increased LVMI. Body surface area was calculated by using formula 0.20247 x Height (m) 0.725 x Weight (Kg) 0.425 according to DuBois and DuBois formula. LVMI for males is 118gm/m2 and 109 gm/m2 in females as per normal Indian population and a value above suggests increase in size of left ventricular mass (hypertrophy). Statistics Chi-square test. Results Mean with ± standard deviation in age (in years) was 50 ± 10.3 and 58± 9.8 in patients without LVH and un patients with LVH respectively. Lateral shift of the apex was seen more in Group II (24.2%) when compared to Group I which showed 4.6%. Apical impulse was found to be 33.3% in Group II as compared to Group I. Chest X ray showed 27.2% in Group II compared to Group I which was 15% for Group I in-terms of cardiac enlargement. Patients having LVH were 51.5% in Group II as compared to 17.9% in Group I for SOKOLOV LYON INDEX and in terms of ROMHILT ESTES, Group II with 42.4% and Group II with 8.9% patients. Patient having concentric LVH as per results of 2 D ECHO patients in Group II was 78.8% compared to patients in Group I which was 11.9%. Conclusion There was a substantial and positive association that shows a strong association between LVMI and increase in size of left ventricular mass (hypertrophy) in hypertensive patients as evident from our study.